2018
DOI: 10.1080/09593985.2018.1429036
|View full text |Cite
|
Sign up to set email alerts
|

The impact of documentation on communication during patient-physiotherapist interactions: A qualitative observational study

Abstract: Documentation is an essential component of physiotherapy practice for clinical, legal, and ethical reasons. Research in other healthcare contexts suggests that documentation impacts upon communication in patient-practitioner interactions. Thus, the objective of this qualitative study was to examine how physiotherapists and their patients communicate during episodes of documentation. The research was informed by ethnomethodology and ethnography. In total, 113 patient-physiotherapist interactions were observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
4
0
3
Order By: Relevance
“…physiotherapy (Schoeb and Hiller, 2018) interactions, and in the data presented here appeared to curtail opportunities for patients to develop their perspectives and 'voice' their underlying concerns.…”
Section: Discussionmentioning
confidence: 82%
“…physiotherapy (Schoeb and Hiller, 2018) interactions, and in the data presented here appeared to curtail opportunities for patients to develop their perspectives and 'voice' their underlying concerns.…”
Section: Discussionmentioning
confidence: 82%
“…Using documentation during the interaction is a widely recognized barrier to effective communication (Cowell, McGregor, et al, 2019; Schoeb & Hiller, 2018). In these findings, the physiotherapists’ sensitivity to the intrusive nature of documentation was manifest in their body comportment and eye gaze away from the documentation and toward the patient (Robinson, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed in these findings how physiotherapists integrated documentation tools to limit their intrusive nature when addressing patients' concerns. Being able to integrate physiotherapy documentation to limit its intrusive nature when addressing patients' concerns may be difficult in current practice given an increasing move toward the use of computerized documentation (Schoeb & Hiller, 2018). It has been suggested that the structure of documentation tools may need reconsideration so that they align more seamlessly with the flow of the conversation (Schoeb & Hiller, 2018).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Various departments have now devised their own specific performa which has sections to be filled with key history points. [2][3][4][5] Problem based learning (PBL) in various ways has become popular in medical schools over the past few years. There was serious division seen between the supporters and the skeptics when the teaching patterns was switched for the first time, and serious concerns were seen regarding the quality and level of knowledge being conveyed to the students.…”
Section: Introductionmentioning
confidence: 99%